FORMATION OF THE COMPUTATIONAL THINKING OF STUDENTS IN THE PROCESS OF COLLABORATIVE LEARNING IN ROBOTICS - Serik, М.; Dimirovski , Georgi; Nurym, Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
In this article, the impact of using robots on learning the programming language in real-time mode during the formation of computational thinking of students in the lesson of educational robotics is considered. The possibility of using constructors during collaborative learning of robotics at school is described. The results of the research showed that the students demonstrated a high level of knowledge and good cooperation when mastering the robotics curriculum together. The authors analyze the features of robotic designers and recommend them for selection and use as necessary in the training process. Programming the movement of the robot makes it possible to observe the work performed by physical robots in real time. In addition, attempts are being made to solve problems related to the lack of a clear definition of computational thinking, which is one of the biggest problems in teaching robotics.